A trajetória política e histórico-normativa do ensino técnico da área de agropecuária no Estado de São Paulo: a história política de transição por decretos de 1882 a 2001 - Silva, Marta Leandro da [UNESP]; Marques, Waldemar (My University, 2014)
This article presents the historical trajectory of agricultural technical education in the State of São Paulo, 1882-2001, with emphasis on regulatory and policy aspects of transition management agencies and disruption in the construction and consolidation of a pedagogical and curricular design of this area of teaching technical and institutional policies of these technical schools. Thus focuses on the major changes in the political-normative and pedagogical and organizational character that shaped the construction of its especificidade.Isto because it is necessary to know the history of technical education 'agricultural' (agricultural area) in order to support the analysis of its configuration current and devise new prospects for your gestão.O Paulista agricultural education was subject to constant political uncertainties as to its principles and fins.As several transfers and reallocations it has undergone through different State Secretariats, reveal political barriers regarding its management and the difficulty of situating it in an appropriate and befitting their purposes locus.

Este artigo apresenta a trajetória histórica do ensino técnico agrícola no Estado de São Paulo, de 1882 a 2001, com destaque para os aspectos normativos e políticos de transição de órgãos gestores e ruptura na construção e consolidação de um projeto pedagógico-curricular desta área do ensino técnico e de políticas institucionais dessas escolas técnicas. Focaliza, assim, as importantes mudanças de caráter político-normativas e pedagógico-organizacionais que delinearam a construção da sua especificidade.Isto porque é necessário conhecer a história do ensino técnico ‘agrícola’ (área agropecuária) a fim de subsidiar a análise de sua configuração atual e divisar novas perspectivas para sua gestão.O ensino agrícola paulista foi alvo de constantes indefinições políticas quanto aos seus princípios e fins.As várias transferências e realocações a que foi submetido passando por diferentes Secretarias Estaduais, revelam os entraves políticos quanto à sua gestão e a dificuldade de situá-lo em um locus apropriado e condizente aos seus fins.
Keywords: Political and normative trajectory; Agricultural technical school; State of Sao Paulo; Trajetória político-normativa; Ensino técnico agrícola; Estado de São Paulo